A study of the crucial Role of Telehealth in Saudi Arabia's Nursing Care Changes (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research investigates how telehealth affects nursing care in Saudi Arabia, with particular attention to how it affects patient satisfaction, healthcare accessibility, and the management of chronic illnesses. The study used a mixed-methods approach to look at the experiences of 300 patients and 200 nurses in both urban and rural settings. It included both qualitative interviews and quantitative surveys. According to the findings, telehealth greatly improves accessibility by removing geographical barriers, and urban nurses use it at a somewhat higher rate than their rural colleagues. The majority of patient satisfaction ratings are positive, which is consistent with other research showing how telehealth can enhance patient experiences. According to the study, telemedicine interventions can effectively manage chronic diseases, including diabetes, as evidenced by a significant decrease in hospital visits and an improvement in medication adherence. Notwithstanding these advantages, considerable impediments were found to include technological hurdles including internet connectivity and digital literacy. The study's conclusions are in line with previous research, highlighting the necessity for continual advancements in technology and education while reiterating the role that telehealth has played in revolutionising healthcare delivery. All things considered, telehealth seems to be a useful instrument for improving nursing care, providing significant advantages and highlighting areas that require further development to reach its full potential in the Saudi healthcare system.